Appreciation for Water Resources Research Reviewers. Issue 10 (3rd October 2018) - Clark, Martyn P.; Bahr, Jean; Bierkens, Marc F. P.; Cai, Ximing; Hall, Jim; Hogue, Terri S.; Luce, Charles H.; Lundquist, Jessica D.; Mackay, D. Scott; van Meerveld, Ilja H. J.; Rajaram, Harihar; Sanchez‐Vila, Xavier; et al.
Abstract : The editors of Water Resources Research express their appreciation to the reviewers of articles submitted to the journal in 2017. Key Point: WRR editors thank the reviewers of the journal in 2017